Legal Pluralism, Decolonization, and Human Rights in Asia - Muhammad Bahrul Ulum; Md. Toriqul Islam (Indonesian Journal of Law and Society, 2022)
Upon the publication of the Indonesian Journal of Law and Society Volume 3 Issue 1 (March 2022), the journal has consistently and timely published bi-annual issues within its starting three-year, with its gradual improvement in terms of management and article publication. This journal also has steadily embraced more authorships from different jurisdictions, in spite of its design as an interdisciplinary forum for academicians, researchers, students, and practitioners to share their ideas and findings after a rigorous peer-review process. In this issue, critical topics spanning from legal pluralism and decolonization to human rights are critically examined. While this edition generally discusses contemporary discourses of how law and society are intertwined in the development of the legal system, most articles also highlight how Asia as a region with diverse and distinct legal traditions takes a considerable role, representing more developing countries as a starting point for a comparative analysis of law and society.